Petty Crime and Cruel Punishment: Lessons from the Mexican Debacle - Calvo, Guillermo A.; Mendoza, Enrique G. (American Economic Review, 2008)
Petty Crime and Cruel Punishment: Lessons from the Mexican DebacleGuillermo A. Calvo; Enrique G. MendozaThe American Economic Review, Vol. 86, No. 2, Papers and Proceedings of the Hundredth andEighth Annual Meeting of the American Economic Association San Francisco, CA, January 5-7,1996. (May, 1996), pp. 170-175.